Benrabia distribution: properties and applications - Mohammed Benrabia; Loai M. A. AlZoubi (My University, 2022)
In this paper, we propose a new two parameter continuous distribution. It is called a Benrabia distribution. Some statistical properties are derived such as: the moment generating function, the moments and related measures, the reliability analysis and related functions. Also, the distribution of order statistics and the quantile function are presented and the R´ enyi entropy is derived. The method of maximum likelihood estimation is used to estimate the distribution parameters. A simulation is performed to investigate the performance of MLE, real data applications show that the proposed distribution can provide a better fit than several well-known distributions.